2016
DOI: 10.1016/j.meegid.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of bovine Noroviruses in Argentinean dairy calves: Circulation of a tentative new genotype

Abstract: Bovine noroviruses are enteric pathogens detected in fecal samples of both diarrheic and non-diarrheic calves from several countries worldwide. However, epidemiological information regarding bovine noroviruses is still lacking for many important cattle producing countries from South America. In this study, three bovine norovirus genogroup III sequences were determined by conventional RT-PCR and Sanger sequencing in feces from diarrheic dairy calves from Argentina (B4836, B4848, and B4881, all collected in 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
1
10
1
1
Order By: Relevance
“…This study not only identified GIII.2, which had been documented previously [18][19][20], but was also able to identify the GIII.1 genotype for the first time ever in Turkey. Like this study, many studies in the USA, Europe, South Korea and Argentina have also detected both genotypes, although the GIII.2 genotype predominates [9,16,21,32,33]. Possible reasons for the low rate of detection of the GIII.1 genotype include the presence of GIII.P2/GIII.1 recombinant BoNoVs and the short duration of viral shedding of this genotype [2].…”
supporting
confidence: 58%
“…This study not only identified GIII.2, which had been documented previously [18][19][20], but was also able to identify the GIII.1 genotype for the first time ever in Turkey. Like this study, many studies in the USA, Europe, South Korea and Argentina have also detected both genotypes, although the GIII.2 genotype predominates [9,16,21,32,33]. Possible reasons for the low rate of detection of the GIII.1 genotype include the presence of GIII.P2/GIII.1 recombinant BoNoVs and the short duration of viral shedding of this genotype [2].…”
supporting
confidence: 58%
“…Norovirus (NV) is a representative strain of the genus Norovirus of family Human Calicivirus (HuCV), which is an icosahedron symmetric single-stranded positive-sense RNA virus with a diameter about 26 to 35 nm 28 . According to the sequencing results, degenerate primers were designed based on the conserved protein with 660 bp of norovirus RdRp.…”
Section: Resultsmentioning
confidence: 99%
“…Noroviruses are known to cause epidemic and sporadic gastroenteritis in humans and animals (Ferragut et al 2016). Phylogenetically, noroviruses are classified into six genogroups (GI-GVI) based on RNA-dependent RNA polymerase (RdRp) and capsid gene (Pourasgari et al 2018).…”
Section: Introductionmentioning
confidence: 99%